WEATHER CONDITIONS IN THE REPUBLIC OF ARMENIA DURING SOUTH CYCLONE PENETRATION (Proceedings of the YSU C: Geological and Geographical Sciences, 2010)
The cyclone fields moving from the South regions to the Republic of Armenia have great influence on the formation of weather conditions of the Republic especially in cold period of the year. Many strong winds, snowstorms and heavy rains are observed by them. The conditions of the South Cyclone formation, the features of the speed and the direction of the movement, the peculiarities of weather conditions in its different parts have been studied on the basis of synoptic charts, satellite images and other statistical data, archived in «Hydrometeorological Centre» of Armenia.
Keywords: South Cyclone; weather conditions